Basic visual perceptual processes in children with typical development and cerebral palsy: The processing of surface, length, orientation, and position. Issue 2 (17th February 2019) - Schmetz, Emilie; Magis, David; Detraux, Jean-Jacques; Barisnikov, Koviljka; Rousselle, Laurence
ABSTRACT: The present study aims to assess how the processing of basic visual perceptual (VP) components (length, surface, orientation, and position) develops in typically developing (TD) children ( n  = 215, 4–14 years old) and adults ( n  = 20, 20–25 years old), and in children with cerebral palsy (CP) ( n  = 86, 5–14 years old) using the first four subtests of the Battery for the Evaluation of Visual Perceptual and Spatial processing in children. Experiment 1 showed that these four basic VP processes follow distinct developmental trajectories in typical development. Experiment 2 revealed that children with CP present global and persistent deficits for the processing of basic VP components when compared with TD children matched on chronological age and nonverbal reasoning abilities.